Beyond the Crisis: Tracking SME Non-Performing Loan in Indonesia Before and After the COVID-19 Stimulus - Cahyono, Eko Fajar; Bayuny, Ahmad Fadlur Rahman; Rusmita , Sylva Alif; Sahabuddin , Mohammad (Review on Islamic Accounting, 2024)
This study evaluates the impact of two Indonesian government economic stimulus packages on the performance of Non-Performing Loans (NPLs) in the Small and Medium Enterprises (SME) financing sector. It compares the NPLs in conventional and rural banks with Non-Performing Financing (NPF) in Islamic commercial and rural banks, before and after the stimulus, during the COVID-19 crisis period. The two policies are in the form of interest/margin subsidies and credit/financing restructuring for debtors in the SMEs sector. The approach used is a quantitative approach with three analytical methods consisting of ANOVA, MANOVA and DiD (Difference in Difference). The secondary data in this study were sourced from official publications of government institutions such as the Financial Services Authority and the Ministry of Finance. The results showed that there were significant differences in the performance of NPL/F of Conventional banks, Islamic Commercial Banks, Conventional Rural banks, and Islamic Rural banks before and after the government's economic stimulus policy was determined.